Key Statistics and Trends in Trade Policy 2022 - United Nations Conference on Trade; Development (United Nations, 2023)
Key Statistics and Trends in Trade Policy is a yearly publication of the Trade Analysis Branch, Division on International Trade and Commodities (DITC), UNCTAD secretariat. The main purpose of this publication is to inform on the use and effects of a wide range of trade policies influencing international trade. The series is part of a larger effort by UNCTAD to analyze trade-related issues of particular importance to developing countries in terms of their participation in the international trading system.